INFLUENCE OF COMPLEMENTARY FEEDING PRACTICE EDUCATION ON MOTHERS’ RESPONSES TO FEEDING TODDLERS: - Elok Yulidaningsih; Tunik Tunik; Yuyun Putri Mandasari (SYNTIFIC, 2026)
Background. Adequate nutrition is essential for the growth of neonates, infants, and toddlers, beginning with exclusive breastfeeding for the first 6 months. After this period, complementary feeding becomes necessary as breast milk alone is insufficient. This approach can lower child mortality under 5 by 6%. Careful introduction of complementary foods is crucial, as errors such as early initiation and inadequate nutrition can lead to health issues. The purpose of this study was to examine the influence of complementary feeding practice education on mothers' responses to feeding toddlers. Research Method. The study employed a pre-experimental one-group pretest-posttest design conducted at the Integrated Health Post (Posyandu) within the Suruh Community Health Center in 2024. The targeted mothers of toddlers under 5 years, utilizing a total sampling method with 50 respondents. Key variables included education on complementary feeding practices, actual feeding practices, and sociodemographic factors such as age, education level, employment status, family income, family size, and toddler characteristics like age, height, and nutritional status. Data collection utilized a comprehensive feeding practices questionnaire (CFPQ) consisting of 54 items, with statistical analyses performed using the Wilcoxon tests. Findings. The test obtained p= 0.000, there is an influence of complementary feeding practice education on mothers' feeding practices for toddlers in the Suruh Community Health Center area. Conclusion. Educational interventions provided by health service providers can effectively change the practice of providing complementary feeding for mothers and improve the growth status of toddlers.